The effect of Ficus Deltoidea’s fruit extraction in different concentration on mouse oocyte / Faezah Ibrahim - Ibrahim, Faezah (Faculty of Applied Sciences, 2008)
Superovulation of female mice with exogenous gonadotrophins is routinely used for increasing the number of eggs ovulated by each female in reproductive and developmental studies. Superovulation is affected by many factors such as hormone concentrations, types of hormone, species of animals, age, time of administrations and many others. Previous reports gave the emphasis on hormone and it dosage. This study was designed to investigate whether the different in concentration of Ficus deltoidea’s fruit extraction can replaces the function of Pragnant Mare’s Serum Gonadotropin to mimic the endogenous effects of follicle stimulating hormones (FSH) in order superovulation process can occur. Ficus deltoidea is popular among medical healer and local people to treat some illness and disease. Based on traditional knowledge, Ficus deltoidea leaves posses characteristics of human reproductive organ and in particular for the female fertility treatment. The different concentrations of Ficus deltoidea’s fruit extracts were given to a different group of mice in a week time and the procedure proceeds with Human Chorionic Gonadotropin (hCG) injection. Fourteen hours later, oocyte retrieval was conducted in the laboratory. After the oocyte retrieval, the oocyte quality and quantity from all concentrations were observed. The oocyte quality and quantity observed includes the total number of oocyte retrieved and the oocyte morphology base on the standard basis. The finding showed that there were slight decreased in oocyte quantity however all oocyte showed normal morphology. Other factors that can influence the result were the strain, age of mice and the environmental factor